ОСОБИСТІСНІ ДИСПОЗИЦІЇ У СТРУКТУРІ ПРИЙНЯТТЯ РІШЕННЯ ОСІБ, ЗАЛЕЖНИХ ВІД ПСИХОАКТИВНИХ РЕЧОВИН - Дарвішов Н. Р. (International Journal of Innovative Technologies in Social Science, 2020)
This article examines the study of decision-making dispositions of substance addicts. The input study model included 21 disposition, that could be categorized as: decision-making styles, personal dispositions and time perspective profile. The study sample consisted of 60 individuals with diagnosed substance addiction. An exploratory factor analysis (EFA) method was used to identify interconnections between decision making dispositions. Four factors of the decision-making process were identified and described: “stress interference”, “stimulation focus”, “spontaneity”, “reflexivity”. The results have been compared with the most common concepts of decision making, particularly, with a two-component decision-making system, and revealed the specifics of the decision-making process of substance addicts not only through individual dispositions but also from a systematic perspective.